2021
DOI: 10.3390/children8020132
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Ventilatory Strategies to Decrease Bronchopulmonary Dysplasia—Where Are We in 2021?

Abstract: Recent advances in neonatology have led to the increased survival of extremely low-birth weight infants. However, the incidence of bronchopulmonary dysplasia (BPD) has not improved proportionally, partly due to increased survival of extremely premature infants born at the late-canalicular stage of lung development. Due to minimal surfactant production at this stage, these infants are at risk for severe respiratory distress syndrome, needing prolonged ventilation. While the etiology of BPD is multifactorial wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…Bronchopulmonary dysplasia (BPD) is a common complication of premature birth [ 38 ]. Exposure to high-oxygen concentrations has been demonstrated to cause simplified lung development, leading to BPD [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bronchopulmonary dysplasia (BPD) is a common complication of premature birth [ 38 ]. Exposure to high-oxygen concentrations has been demonstrated to cause simplified lung development, leading to BPD [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, previous research [23] indicated that infants on endotracheal tube for 4-7 days are likely to have BPD or death compared with NIPPV (p < 0.02) and NCPAP (p < 0.01) groups. Researchers also suggested that prematurity should wean from NIPPV to NCPAP after the acute phase to minimize lung injury and promote lung growth [24].…”
Section: Discussionmentioning
confidence: 99%
“…In many infants, the lung injury that leads to BPD begins with abnormal lung development before birth (for example, when the lungs are tiny for their gestational period, chorioamnionitis, and tobacco exposure) [22]. When combined with other risk factors such as surfactant inadequacy, ventilation-associated lung injury, nutritional deficiency, oxygen radical's toxicity, perinatal and postnatal infections, and inflammatory conditions, the vicious circle of lung injury hinders pulmonary vasculature development, eventually leading to BPD [23]. This section examines the key etiology and how they lead to BPD development.…”
Section: Etiology Of Bronchopulmonary Dysplasiamentioning
confidence: 99%